High electron mobility and insights into temperature-dependent scattering mechanisms in InAsSb nanowires - Boland, JL; Amaduzzi, F; Sterzl, S; Potts, H; Herz, LM; Morral, A; Johnston, MB (American Chemical Society, 2018)
InAsSb nanowires are promising elements for thermoelectric devices, infrared photodetectors, high-speed transistors, as well as thermophotovoltaic cells. By changing the Sb alloy fraction the mid-infrared bandgap energy and thermal conductivity may be tuned for specific device applications. Using both terahertz and Raman noncontact probes, we show that Sb alloying increases the electron mobility in the nanowires by over a factor of 3 from InAs to InAs0.65Sb0.35. We also extract the temperature-dependent electron mobility via both terahertz and Raman spectroscopy, and we report the highest electron mobilities for InAs0.65Sb0.35 nanowires to date, exceeding 16,000 cm2 V–1 s–1 at 10 K.